Dynamic Creep Performance of Hot Mix Asphalt Mixture Incorporating Fibre - Taher, M. N. M; Aman, M. Y.; Nazir, M. A. M; Bujang, H. (International Journal of Integrated Engineering, 2022)
Permanent deformation is one of the distress that develops gradually as the number of load applications increases and appears as longitudinal depressions in the wheel paths and small upheavals to the sides. For this reason, numerous studies conducted on modification asphalt binder or mixture by various fibre. This paper presents the evaluation of creep modulus and permanent deformation of modified asphalt mixture with fibres. In order to envisage the modified asphalt mixture, Forta-fi, Kenaf and PET was blended to estimate the creep properties and rut depth value at different loading pattern. Superpave mix design method was employed with NMAS 12.5mm to obtain the optimum bitumen content established at 4% air void. In the respect, bitumen 60/70 penetration grade with 0.5% of Forta-Fi, 0.1% Kenaf fibre and 0.5% PET by weight of asphalt mixture were prepared. Dynamic Creep Test was performed in accordance to the EN 12697-25:2005 guidelines using the Universal Testing Machine (UTM). As the result, the minimum value of permanent deformation was found at 0.5% of PET. Based on these studies, adding a minimum percent of PET in the asphalt mixture shows a better resistance to rutting deformation and enable a better understanding of the properties in modified asphalt mixtures.